Chemical Composition of Active Compounds in Standardized Cinnamon Simplicia (Cinnamomum verum) - Sentot Joko Raharjo; Dewi Ratih Tirto Sari; Yanty Maryanty; Ita Tresnowati; Ernanin Dyah Wijayanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Cinnamon (Cinnamomum verum) is widely recognized as a spice with a distinctive aroma that has a variety of applications in the culinary and health industries, due to its diverse active compounds. Standardization is essential to ensure the quality and uniformity of cinnamon raw materials. Previous studies primarily focused on identifying the most abundant compounds and bioactivity testing. However, a comprehensive analysis of the chemical composition of active compounds in different solvent extracts and essential oils has not been fully reported. This study aims to explore the chemical composition of active compounds in standardized cinnamon simplicia. Standardization parameters include water-soluble extractive, ethanol-soluble extractive, moisture content, ash content, microbial contamination levels, and qualitative and quantitative phytochemical analysis. Cinnamon was extracted using water, n-hexane, and steam distillation to obtain water extract, n-hexane extract, and essential oil, respectively, which were then analyzed by LC-MS and GC-MS. In general, all parameters set for the standardization of cinnamon simplisia met the applicable quality standards. The total phenolic content obtained was 3.99 ± 0.14 mgGAE/g, flavonoid content was 1.54 ± 0.10 mgQE/g, and total terpenoid content was 1.35 ± 0.13 mg/g. Furthermore, this study identified that the dominant active compounds in water extracts were polyphenols; n-hexane extracts contained major active compounds in terpenoids. At the same time, cinnamon essential oil showed the largest content of cinnamaldehyde. These findings provide important information regarding the chemical composition of cinnamon and its contribution to potential applications in the pharmaceutical and natural products industries.